Tissue-specific transcriptomics reveals a central role of CcNST1 in regulating the fruit lignification pattern in Camellia chekiangoleosa, a woody oil-crop - Chao Yan; Ziyan Nie; Zhikang Hu; Hu Huang; Xianjin Ma; Sijia Li; Jiyuan Li; Xiaohua Yao; Hengfu Yin (Forestry Research, 2022)
Fruit lignification is of significant economic importance because it affects the quality of fruit and the production of seed oil. The specified lignification pattern in Camellia chekiangoleosa fruits plays critical roles in its seed oil yield, but little is known about how this lignification process is regulated. Here, we report on a comprehensive tissue-specific transcriptomics analysis conducted for C. chekiangoleosa fruit. By mining the differentially expressed genes, we found that lignin biosynthesis and transcriptional regulation pathways were significantly enriched in the lignified tissues. The homolog of NST-like transcription factor, CcNST1, was highly expressed in lignified seed coat and endocarp tissues; transgenic analyses of CcNST1 in Arabidopsis and hybrid poplar revealed the enhanced lignification levels of various tissues. Gene expression analysis of the transgenic lines uncovered potential downstream genes involved in the regulation of lignin biosynthesis. This work provides a valuable gene expression resource and identified the pivotal role of CcNST1 in regulating the lignin biosynthesis underlying fruit lignification.